Associations of frailty with health care costs – results of the ESTHER cohort study. Issue 1 (December 2016) - Bock, Jens-Oliver; König, Hans-Helmut; Brenner, Hermann; Haefeli, Walter; Quinzler, Renate; Matschinger, Herbert; Saum, Kai-Uwe; Schöttker, Ben; Heider, Dirk
Abstract Background The concept of frailty is rapidly gaining attention as an independent syndrome with high prevalence in older adults. Thereby, frailty is often related to certain adverse outcomes like mortality or disability. Another adverse outcome discussed is increased health care utilization. However, only few studies examined the impact of frailty on health care utilization and corresponding costs. The aim of this study was therefore to investigate comprehensively the relationship between frailty, health care utilization and costs. Methods Cross sectional data from 2598 older participants (57–84 years) recruited in the Saarland, Germany, between 2008 and 2010 was used. Participants passed geriatric assessments that included Fried's five frailty criteria: weakness, slowness, exhaustion, unintentional weight loss, and physical inactivity. Health care utilization was recorded in the sectors of inpatient treatment, outpatient treatment, pharmaceuticals, and nursing care. Results Prevalence of frailty (≥3 symptoms) was 8.0 %. Mean total 3-month costs of frail participants were €3659 (4 or 5 symptoms) and €1616 (3 symptoms) as compared to €642 of nonfrail participants (no symptom). Controlling for comorbidity and general socio-demographic characteristics in multiple regression models, the difference in total costs between frail and non-frail participants still amounted to €1917;p  < .05 (4 or 5 symptoms) and €680;p  < .05 (3 symptoms). Among the 5 symptoms of frailty, weight loss and exhaustion were significantly associated with total costs after controlling for comorbidity. Conclusions The study provides evidence that frailty is associated with increased health care costs. The analyses furthermore indicate that frailty is an important factor for health care costs independent from pure age and comorbidity. Costs were rather attributable to frailty (and comorbidity) than to age. This stresses that the overlapping concepts of multimorbidity and frailty are both necessary to explain health care use and corresponding costs among older adults.